Scientific Paper Entitled: Professional Seniority On The Quality Of Health Care Services From The Perspective Of Health Personnel In The Government Health Sector In The Kingdom Of Saudi Arabia (Journal of Namibian Studies : History Politics Culture, 2022)
The professional seniority of health personnel is considered an essential factor in ensuring the quality of health services, as they possess the experience and knowledge necessary to provide health care at the highest level.  However, achieving the quality of health services requires a careful analysis of the impact of professional seniority on the provision of health services, by understanding the viewpoints of health cadres in the government sector. The study aimed to identify the role of professional seniority on the quality of health care services from the perspective of health cadres in The government health sector in the Kingdom of Saudi Arabia. The descriptive survey method was used to suit the nature and objectives of the study. A questionnaire was designed targeting health personnel in the government sector. The results of the study highlighted the existence of a strong positive relationship between professional seniority and the quality of health care services from the point of view of health workers in the sector.  The Government Health Ministry in the Kingdom of Saudi Arabia recommended the need to provide a work environment that encourages continuous learning and exchange of experiences among health personnel.